PENGEMBANGAN MEDIA POP-UP DONGENG DIGITAL (POPONA) UNTUK SISWA SEKOLAH DASAR - Moh. Dehiyo, Sofiyanti; Husain, Rusmin; Monoarfa, Fidyawati; Triyanty Pulukadang, Wiwy; Husain, Rustam (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
The ability to read fairy tales in elementary school students is still relatively low, one of which is caused by the lack of supporting learning media. In fact, fairy tales as folk prose stories that are fictitious and contain moral messages have great potential in awakening imagination, fostering creativity, and instilling character values in students. This study aims to develop digital pop-up fairy tale learning media (POPONA) to improve elementary school students' fairy tale reading skills. This research is a research and development using the 4D model (define, design, develop, and disseminate). The research subjects consisted of media experts, linguists, material experts, practitioners, and 28 fifth grade students. Data collection techniques included observation, interviews, and questionnaires, with instruments in the form of observation sheets, interviews, expert validation, and teacher and student response sheets. The data were analyzed qualitatively and quantitatively to measure the feasibility and effectiveness of the media. The results showed that POPONA media was included in the very feasible category, with the results of expert validation obtaining an average percentage of 96.6% and teacher and student response tests of 92%. In addition, students' ability to read fairy tales when using POPONA media reached a percentage of 98.01%. Thus, it can be concluded that digital pop-up fairy tale media (POPONA) is very feasible to use as a learning media in improving students' reading ability. ABSTRAK Kemampuan membaca dongeng pada siswa sekolah dasar masih tergolong rendah, salah satunya disebabkan oleh kurangnya media pembelajaran yang mendukung. Padahal, dongeng sebagai cerita prosa rakyat yang bersifat fiktif dan mengandung pesan moral, memiliki potensi besar dalam membangkitkan imajinasi, menumbuhkan kreativitas, serta menanamkan nilai-nilai karakter pada siswa. Penelitian ini bertujuan untuk mengembangkan media pembelajaran pop-up dongeng digital (POPONA) guna meningkatkan kemampuan membaca dongeng siswa sekolah dasar. Penelitian ini merupakan penelitian pengembangan (research and development) yang menggunakan model 4D (define, design, development, dan disseminate). Subjek penelitian terdiri atas ahli media, ahli bahasa, ahli materi, praktisi, dan 28 siswa kelas V SD. Teknik pengumpulan data meliputi observasi, wawancara, dan angket, dengan instrumen berupa lembar observasi, wawancara, validasi ahli, serta lembar respon guru dan siswa. Data dianalisis secara kualitatif dan kuantitatif untuk mengukur kelayakan media. Hasil penelitian menunjukkan bahwa media POPONA termasuk dalam kategori sangat layak, dengan hasil validasi ahli memperoleh rata-rata persentase 96,6% dan uji respon guru dan siswa sebesar 92%. Selain itu, kemampuan membaca dongeng siswa saat menggunakan media POPONA mencapai persentase 98,01%. Dengan demikian, dapat disimpulkan bahwa media pop-up dongeng digital (POPONA) sangat layak digunakan sebagai media pembelajaran dalam meningkatkan kemampuan membaca dongeng pada siswa sekolah dasar.